Temperature Exerts Control of Bacillus cereus Emetic Toxin Production on Post-transcriptional Levels - Kranzler, Markus; Stollewerk, Katharina; Rouzeau-Szynalski, Katia; Blayo, Laurence; Sulyok, Michael; Ehling-Schulz, Monika (Frontiers in Microbiology, 2016)
In recent years, the emetic toxin cereulide, produced by Bacillus cereus, has gained high relevance in food production and food safety. Cereulide is synthesized nonribosomal by the multi-enzyme complex Ces-NRPS, which is encoded on a megaplasmid that shares its backbone with the Bacillus anthracis pX01 toxin plasmid. Due to its resistance against heat, proteolysis and extreme pH conditions, the formation of this highly potent depsipeptide toxin is of serious concern in food processing procedures including slow cooling procedures and /or storage of intermediate products at ambient temperatures. So far, systematic data on the effect of extrinsic factors on cereulide synthesis has been lacking. Thus, we investigated the influence of temperature, a central extrinsic parameter in food processing, on the regulation of cereulide synthesis on transcriptional, translational and post-translational levels over the growth temperature range of emetic B. cereus. Bacteria were grown in 3°C interval steps from 12°C to 46°C and cereulide synthesis was followed from ces gene transcription to cereulide toxin production. This systematic study revealed that temperature is a cardinal parameter, which primarily impacts cereulide synthesis on post-transcriptional levels, thereby altering the composition of cereulide isoforms. Our work also highlights that the risk of cereulide production could not be predicted from growth parameters or sole cell numbers. Furthermore, for the first time we could show that the formation of the recently identified cereulide isoforms is highly temperature dependent, which may have great importance in terms of food safety and predictive microbiology. Notably the production of isocereulide A, which is about 10-fold more cytotoxic than cereulide, was specifically supported at low temperatures.